KICHIK HUDUDLAR AHOLISI TARKIBI VA GEODEMOGRAFIK RIVOJLANISHI - Tojieva, Z.N.; Do‘smonov, F.A. (SCIENCE and SOCIETY, 2025)
The article examines the socio-demographic development of a small territory, changes in the dynamics of the population, the composition of the population, family, age composition of the population by the section of citizens' meetings of the mahalla.
Keywords: territory; economic, social and demographic development; population; mahalla; civil society of mahalla; Fergana; Greater Namangan; Chartok; population growth